2023
DOI: 10.2147/amep.s393051
|View full text |Cite
|
Sign up to set email alerts
|

Education and Mentoring of Specialist Pediatric Palliative Care Medical and Nursing Trainees: The Quality of Care Collaborative Australia

Abstract: Background The Quality of Care Collaborative Australia (QuoCCA) builds capability in the generalist and specialist paediatric palliative care (PPC) workforce throughout Australia. It supports regional and community services to provide care close to families’ homes, as well as building expertise in tertiary centers. Objective Medical Fellows and Nurse Practitioner candidates (specialist trainees) were funded by QuoCCA at four tertiary hospitals throughout Australia suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Shares of comfort-oriented care provided by nurses to citizens generate holistic responses to complex stimuli, leading to improved comfort while seeking behavior directed at strengthening health. [ 28 , 29 ] This care is provided through interpersonal processes inherent in self-construction as well as the situations faced both naturally and socially from birth to death. [ 30 ] Numerous nursing researchers have explored comfort care as a phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Shares of comfort-oriented care provided by nurses to citizens generate holistic responses to complex stimuli, leading to improved comfort while seeking behavior directed at strengthening health. [ 28 , 29 ] This care is provided through interpersonal processes inherent in self-construction as well as the situations faced both naturally and socially from birth to death. [ 30 ] Numerous nursing researchers have explored comfort care as a phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A standard program of work has been recommended for the QuoCCA education and mentoring framework. 14 This should include strategies for personal wellbeing, professional issues, life balance, management of distress, networking and career counselling. 41 …”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Although these and other studies showed the opportunities to promote wellbeing through mentoring, it was unknown how this could be applied in the context of the specialised area of PPC through the QuoCCA education and mentoring framework. 14 The purpose of this study was to explore the perspectives and experiences of clinicians who had occupied the QuoCCA MF and NP trainee positions in the specialised area of PPC to identify the ways in which they were supported and mentored to maintain their wellbeing and facilitate sustainable practice.…”
Section: Introductionmentioning
confidence: 99%
“…Practicar habilidades clínicas fue beneficioso en guardia, visitas domiciliarias, apoyo familiar, prescripción de medicamentos y trabajo con equipos para desarrollar planes de tratamiento. (Slater & Herbert, 2023) Etapa 17…”
Section: Etapas Etapa 16 Médicos Especialistasunclassified